Ptiliidae of the Maritime Provinces of Canada (Coleoptera): new records and bionomic notes - Majka, Christopher G.; Sörensson, Mikael (Zootaxa, 2007)
The Ptiliidae of the Maritime Provinces of Canada is surveyed. Twenty-nine new provincial records from the Maritime Provinces of Canada are reported including the first records of the family from Prince Edward Island. Fourteen species are recorded for the first time for the Maritime Provinces as a whole. Acrotrichis josephi (Matthews) is recorded for the first time in eastern North America and Acrotrichis haldemani (LeConte) is recorded for the first time in Canada. The genus Pteryx is reported for the first time in Canada. At least 29 species of Ptiliidae are now known to occur in the region. The fauna is briefly discussed in terms of its overall composition, introduced species, and species associated with particular habitats. Saproxylic species found in mature forests are discussed and attention is drawn to their possible relationship to undisturbed forest conditions and the scarcity of old-growth habitats in the region.